Thin film growth of CaFe2As2 by molecular beam epitaxy. (3rd December 2015) - Hatano, T; Kawaguchi, T; Fujimoto, R; Nakamura, I; Mori, Y; Harada, S; Ujihara, T; Ikuta, H
Abstract: Film growth of CaFe2 As2 was realized by molecular beam epitaxy on six different substrates that have a wide variation in the lattice mismatch to the target compound. By carefully adjusting the Ca-to-Fe flux ratio, we obtained single-phase thin films for most of the substrates. Interestingly, an expansion of the CaFe2 As2 lattice to the out-of-plane direction was observed for all films, even when an opposite strain was expected. A detailed microstructure observation of the thin film grown on MgO by transmission electron microscope revealed that it consists of cube-on-cube and 45°-rotated domains. The latter domains were compressively strained in plane, which caused a stretching along the c -axis direction. Because the domains were well connected across the boundary with no appreciable discontinuity, we think that the out-of-plane expansion in the 45°-rotated domains exerted a tensile stress on the other domains, resulting in the unexpectedly large c -axis lattice parameter, despite the apparently opposite lattice mismatch.